Licensing Services Innovation Establishing Buildings in One Stop Integrated Services in North Jakarta - Hakim, Lukman; Basuki, Johanes; Soemartono, Triyuni; Kusworo, Kusworo (International Journal for Educational and Vocational Studies, 2019)
This article aimed to determine and analyses the implementation of innovation forms as well as the factors supporting and inhibiting the implementation of innovation in local government level. The research was conducted in north Jakarta. The research conducted One-Stop Integrated Service Office. The results showed that the licensing office innovated to accelerate building permits, which was easy and inexpensive with describe establishing building procedures, then start a variety of innovations carried out by One-Stop Integrated Service Office one day, register IMB online, IMB 3.0, bleaching IMB. And this is an important requirement for the business world. In providing services to business operators, efforts are needed from the government to implement good services by applying transparent, participatory and accountable principles, so that the community as a group that is served will get good service. Supporting factors for service innovation in the three regions were regulation and commitment of the local governments while the inhibiting factors of innovation implementation were the limited fund and incompetent personnel in service duties.